Learning about sound - AIMS Multimedia (Chatsworth, CA : AIMS Multimedia, 1997)
Juvenile literature about sound that includes video, bulletin board, quiz, test, notes for the teacherand information in PDF format also provided in a floppy disc
Title from title screen
Installation guide : Macintosh, drag folder to hard drive, the double click on the program icon ; Windows, run'INSTALLE.EXE' from the cd-rom, then double click the program icon
Keywords: Sound -- Juvenile literature; Sound